96. Assessing the Impact of the Meningitis/encephalitis Diagnostic Panel on Antimicrobial Stewardship. (31st December 2020) - Garellek, Jonathan; Doan, Thien-Ly; Varghese, Shawn; Schwartz, Rebecca; Rasul, Rehana; Donaghy, Henry
Abstract: Background: The multiplex polymerase chain reaction (PCR) test for meningitis/encephalitis (ME) is an assay that is available to detect 14 organisms in 2 hours from the cerebral spinal fluid. The primary objective was to assess the clinical impact of this assay on antimicrobial stewardship. Methods: This is an IRB-approved, retrospective cohort study of a random sample of patients admitted between 7/2015 - 12/2018, stratified by season. A chart review was performed to collect: demographics, microbiology/treatment data, length of stay, hospital readmissions, and mortality. Differences for ME PCR versus culture only were assessed using Chi-square test or Fisher's exact test. Time to de-escalation of empiric therapy was compared using the log-rank test. Results: The study consisted of 241 patients, of whom 161 (66.8%) had CSF-PCR testing performed. Mean age was 51.76. There was an even distribution of males and females. Aside from patients with HIV, who were more represented in the standard period, there were no differences by comorbidity. The etiology of meningitis was greater in the PCR compared to the non-PCR group (10.5% vs. 2.5% in PCR and non-PCR respectively). Time to de-escalation of empiric therapy was significantly shorter in the PCR period (median [IQR]: 43.06 [26.9–47.7] vs. 64.62 [37.18–83.33], P< 0.004). Total days of therapy of antibiotics was longer among the PCR group, but not statistically significant (median [IQR] = 4 [1–7] vs. 2 [1–4], P=0.121). Median length of stay was higher in the PCR period compared to the standard group (median [IQR]: 9 [6 - 15] vs. 5.5 [3 - 8.5], P< 0.004). Readmission rates did not differ (PCR 13.7% vs. non-PCR 16.3%, P=0.592). More died during the PCR period (8.6% vs. 3.8%, P=0.16) but this was not statistically significant. Conclusion: The ME PCR was associated with an earlier time to antibiotics de-escalation. Patients that had the PCR test performed had more days of therapy and longer length of stay, but this is likely due to a higher rate of pathogen diagnosed. There was no association in readmissions. The initiation of rapid diagnostic testing in a healthcare settings has the potential to improve patient outcomes and may help antimicrobial stewardship by shortening the time to de-escalating antimicrobials and offering appropriate targeted therapy. Disclosures: All Authors : No reported disclosures